Peran UMKM Dalam Pembangunan dan Kesejahteraan Masyarakat di Kabupaten Deli Serdang - Maulida Qadisyah; Ainatul Hasanah; Hasriyati Hanum; Nurhayati Harahap (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
This research aims to determine the role of Micro, Small and Medium Enterprises (MSMEs) in driving development and improving the welfare of the people of Deli Serdang Regency. This research uses qualitative and quantitative approaches to evaluate the contribution of MSMEs to local economic growth and improving people’s living standards. The research results show that MSMEs not only act as drivers of the local economy, but also as significant empowerment agents for small business actors in the region. Through their contribution to the local economic sector, MSMEs not only create jobs, but also increase people’s income. By focusing on developing local products and empowering small businesses, MSMEs play a key role in strengthening the regional economic ecosystem.